95.5k views
5 votes
Can you make y=-(x+2)^2+17 standard form?

2 Answers

6 votes

Answer:

y = -x² -4x +13

Explanation:

y = - ( x+2)² + 17

y = - x² -4x -4 +17

y = -x² -4x +13

User Sebastialonso
by
4.7k points
1 vote

Answer:

y = - x² - 4x + 13

Explanation:

The equation of a parabola in standard form is

y = ax² + bx + c ( a ≠ 0 )

Given

y = - (x + 2)² + 17 ← expand factor using FOIL

= - (x² + 4x + 4) + 17 ← distribute parenthesis by - 1

= - x² - 4x - 4 + 17 ← collect like terms

y = - x² - 4x + 13

User Francis Pelland
by
4.5k points